The Educational Functions of Inquiry in Masnavi-ye-Ma‘navi with Emphasis on the First Book - Fateme Davari Dolatabadi; Mohsen Mohammadi Fesharaki; Mohammad Hossein Heidari (تربیت اسلامی, 2023)
Molavi is one of the poets and writers who has paid much attention, in his works, to the influence of words on the audience and to arousing them. One of the reasons for this claim is, in addition to his direct references to observe the audience's situation, that there are convergent, explanatory, and divergent questions in Masnavi-ye-Ma‘navi, which activates thought and creates positive change. The present study has first collected the questions in the First Book of Masnavi-ye-Ma‘navi, then, while separating educational questions, it has provided educational functions for them based on their arousal in the audience. Having studied and selected the sample, and collected the data, the researchers used the method of qualitative content analysis to analyze the data. The result of this study is that the educational questions of the First Book of Masnavi-ye-Ma‘navi are extracted in functions such as creating reminders, accepting inability, paying attention to and focusing on a subject, revealing neglect and ignorance, by removing neglect, demanding reasoning, expanding insight and knowledge, removing doubt, expressing regret and trying to compensate, asking Allah, and asking others. Teachers can use questions in the functions that were extracted from Masnavi-ye-Ma‘navi to rouse, resolve training and educational problems, develop students’ creativity and logical thinking.